Media Virtual Reality Berbasis Pemodelan 3D untuk Edukasi Warisan Budaya Paseban Tri Panca Tunggal - Yulyanto; Fachri El'Kariem; Rika Nugraha (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The erosion of cultural heritage literacy among younger generations is a pressing challenge in Indonesia's digitizing society. Paseban Tri Panca Tunggal, a Sundanese heritage building constructed in 1840 in Cigugur, Kuningan, West Java, embodies significant philosophical and architectural values of the Sunda Wiwitan belief system, yet remains largely inaccessible to students through conventional educational approaches. This study presents the design and implementation of a 3D modeling-based Virtual Reality (VR) educational medium for this heritage site using the Multimedia Development Life Cycle (MDLC) framework. Blender was used for hardsurface 3D modeling, Unity for interactive integration, and Spatial.io for metaverse-based VR deployment, producing an immersive learning experience accessible via web browser, Android devices, and VR headsets. Nine key architectural elements, each bearing distinct philosophical meaning, were digitally reconstructed with interactive audio narration and informational pop-ups. Expert media validation yielded 4.3/5.0 (Very Feasible), object accuracy validation scored 3.5/5.0 (Feasible), and user testing with 36 Grade-5 primary students produced 4.21/5.0 (84.2%, Very Feasible). These results demonstrate that VR-based 3D modeling is an effective medium for cultural heritage education, offering a replicable model for digital preservation of locally significant heritage sites in Indonesia. As the first VR educational medium specifically designed for Paseban Tri Panca Tunggal, this work contributes a replicable digital preservation framework for locally significant heritage sites across Indonesian educational contexts.